Bioinspired morphing fins to provide optimal maneuverability, stability, and response to turbulence in rigid hull AUVs. (1st May 2022) - Randeni, Supun; Mellin, Emily M; Sacarny, Michael; Cheung, Skyler; Benjamin, Michael; Triantafyllou, Michael
Abstract: By adopting bioinspired morphing fins, we demonstrate how to achieve good directional stability, exceptional maneuverability, and minimal adverse response to turbulent flow, properties that are highly desirable for rigid hull AUVs, but are presently difficult to achieve because they impose contradictory requirements. We outline the theory and design for switching between operating with sufficient stability that ensures a steady course in the presence of disturbances, with low corrective control action; reverting to high maneuverability to execute very rapid course and depth changes, improving turning rate by 25% up to 50%; and ensuring at all times that angular responses to external turbulence are minimized. We then demonstrate the developments through tests on a 1 m long autonomous underwater vehicle, named Morpheus . The vehicle is capable of dynamically changing its stability-maneuverability qualities by using tuna-inspired morphing fins, which can be deployed, deflected and retracted, as needed. A series of free-swimming experiments and maneuvering simulations, combined with mathematical analysis, led to the design of optimal retractable morphing fins.